2022
DOI: 10.1186/s12905-022-02041-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anticancer therapy on the quality of life of Sudanese patients with breast cancer at Khartoum oncology hospital

Abstract: Background Chemotherapy-related toxicity affects the quality of life (QOL) of patients with cancer. Measuring the QOL in breast cancer (BC) patients has been the focus of clinical practices and research in recent decades. This study aimed to assess the impact of BC medications on QOL of Sudanese patients with BC. Methods A cross-sectional study was conducted in Khartoum Oncology Hospital, Sudan, from November 2020 to March 2021. All patients diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In total, 48 studies were included, comprising quantitative 28–51 ( n = 24), qualitative 52–74 ( n = 23) and mixed methods 75 ( n = 1) studies. All included studies were published between 1998 and 2022 and represented data from countries ( n = 10) in Africa and covered the five regions of Africa (central, eastern, southern, western, and northern) with at least one study from each region.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 48 studies were included, comprising quantitative 28–51 ( n = 24), qualitative 52–74 ( n = 23) and mixed methods 75 ( n = 1) studies. All included studies were published between 1998 and 2022 and represented data from countries ( n = 10) in Africa and covered the five regions of Africa (central, eastern, southern, western, and northern) with at least one study from each region.…”
Section: Resultsmentioning
confidence: 99%
“…During and after treatment, commonly experienced physical symptoms included fatigue, trouble sleeping, pain, burnout, sexual dysfunction, appetite loss, diarrhoea, constipation, nausea, and vomiting, alongside worry relating to body image and hair loss 32,37,38,40,42 . Studies reported that women generally had low quality‐of‐life scores across multiple domains during treatment cycles 37,38,41,44 and that younger women, in particular, were likely to experience reduced emotional well‐being 41 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations